1994
DOI: 10.1117/12.171231
|View full text |Cite
|
Sign up to set email alerts
|

<title>Detection of explosives, narcotics, and taggant vapors by an ion mobility spectrometry particle detector</title>

Abstract: ABSTRACrMethods of analyzing vapors in an IMS explosives/narcotics detectr that is primarily designed for particle collection were investigated, with emphasis on nitroglycerin explosive, and &'etic and benzoic acid contaminants in narcotics. A preconcentration step is required because expected vapor concentrations are low. NO adsorption and retention behaviour on conted teflon ifiters that are compatible with the IMS sample desorption system is repMied, including the effects of adsorbent, and sampling flow rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…A variety of collection techniques for portal screening have been described. These include vapor suction or particle removal by wiping or vacuuming; collection on metal screens, tubes, plates, or Teflon filters; and thermal desorption by activating a heater in the collection device or insertion of the collecting surface into a heater (34,(36)(37)(38). A particularly detailed discussion of the collector, a spiral ribbon metal surface collector/concentrator, used in the Thermedics Detection EGIS GC/CD device has been given (39).…”
Section: Collectors Preconcentrators and Hand-held Samplersmentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of collection techniques for portal screening have been described. These include vapor suction or particle removal by wiping or vacuuming; collection on metal screens, tubes, plates, or Teflon filters; and thermal desorption by activating a heater in the collection device or insertion of the collecting surface into a heater (34,(36)(37)(38). A particularly detailed discussion of the collector, a spiral ribbon metal surface collector/concentrator, used in the Thermedics Detection EGIS GC/CD device has been given (39).…”
Section: Collectors Preconcentrators and Hand-held Samplersmentioning
confidence: 99%
“…Estimates in the literature for the limits of detection of several commercially available devices do indeed vary by more than an order of magnitude. For example, the Barringer IONSCAN series of instruments (36,164,165) has been evaluated by Fetterolf and coworkers (166)(167)(168)(169) to have 200-pg limits of detection for several of the common explosives. Hallowell et al (170) reported an RDX detection limit of approximatedly 20 pg using a PCP Model 110, and Davies et al (50) reported calibration studies using the same device that, for instance, yielded 95% confidence limits on an observation of 5 pg RDX of ±14 pg.…”
Section: Ion Mobility Spectrometrymentioning
confidence: 99%
“…This ionization mechanism produces positively and negatively charged analytes, with an efficiency that is dependent on the absolute difference in proton affinity between the analyte and the activated reagent gas. Ions are then pulsed into the drift cell and detected using a Faraday plate. , For this study, ion mobility spectra of all compounds were recorded on a standard IONSCAN 400B system as described previously. , Swabs were introduced into the IONSCAN 400B IMS system and heated to 224 °C, thermally desorbing the analytes Samples were analyzed for a total of 8 s (positive ion mode) and 7.5 s (negative ion mode) and were acquired using the standard 400B software.…”
Section: Methodsmentioning
confidence: 99%